V-Shaped amphiphilic polymer brushes grafted on cellulose nanocrystals: Synthesis, characterization and properties. (July 2021) - Zhou, Jianhua; Li, Hong; Li, Yannan; Li, Xiang
Abstract: Cellulose nanocrystals (CNCs) were modified using an amphiphilic triblock copolymer [poly(2-(dimethylamino) ethyl methacrylate)- b -poly(glycidyl methacrylate)- b -poly(2, 2, 3, 4, 4, 4-hexafluorobutyl acrylate) (PDMAEMA- b -PGMA- b -PHFBA)] bearing epoxy functionalities located in middle segment of PGMA, which were used to react with the hydroxyl groups on the surface of the CNCs. The triblock copolymer was synthesized via a reversible addition fragmentation chain transfer (RAFT) polymerization reaction between 2-(dimethylamino) ethyl methacrylate, glycidyl methacrylate and 2, 2, 3, 4, 4, 4-hexafluorobutyl acrylate, and characterized using 1 H-NMR spectroscopy and size exclusion chromatography (SEC). The successful modification of the CNCs was demonstrated by means of FT-IR, TGA, TEM, XRD and XPS. In addition, the surface properties of the modified CNCs were studied using water contact angle and surface tension studies. When compared with the pristine CNCs, the modified CNCs exhibited a higher contact angle and lower surface tension. Good dispersion of the modified CNCs was observed in different polar solvents, such as water, THF, DMF, CHCl3 and toluene. The modified CNCs exhibited pH responsive properties, which were measured using dynamic light scattering (DLS). In addition, the stability of Pickering emulsions stabilized by PDMAEMA- g -CNC- g -PHFBA decreased with time or increasing pH. The droplet size increased gradually upon increasing the pH. This work provides a method to design sophisticated CNC-based materials, which benefit from both the intrinsic properties of the CNCs and the new characteristics conferred by the multifunctional grafted chains. Graphical abstract: PDMAEMA- g- CNC- g -PHFBA were prepared by grafting PDMAEMA- b -PGMA- b -PHFBA onto the CNCs surface using a feasible ring-opening reaction between the epoxy groups in the middle of the triblock copolymer and the hydroxyl groups on the CNCs surface. The PDMAEMA- b -PGMA- b -PHFBA triblock copolymer was grafted onto the CNCs surface in a V-shape manner. Image 1 Highlights: CNCs were modified using a pH stimuli-responsive amphiphilic triblock copolymer. The amphiphilic triblock copolymer was prepared using RAFT polymerization. Covalent grafting copolymer on CNCs can be achieved using "grafting to" methods. The amphiphilic copolymer was grafted on the surface of CNCs in a V-shape manner. The modified CNCs present good amphiphilicity and pH-responsive properties.